IN VIVO UTILIZATION OF SEAFOOD PROCESSING WASTES FOR CULTIVATION OF THE MEDICINAL MUSHROOM (GANODERMA LUCIDUM) USING AGRO-INDUSTRIAL WASTE - LAKSHMI, S.SUBBU (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective Â To examine the utilization of seafood processing wastes for artificial cultivation of medicinal mushroom and composting in laboratory condition. Â Â Method Â The selected agro-industrial wastes (e.g., coir pith, woodchips, sugarcane bagasse) were mixed with fishery waste in specific ratio (1:1).The substrates which are not mixed with fishery waste are regarded as control. All the above materials (1:1,control) were allowed to decompose about 15 days. The composted materials were placed in heat resistant transparent polyethylene bags. Each sterile bag was then aseptically inoculated with G.lucidum. The bags were then incubated under ambient temperature and controlled humidity. Â Â Results Â The maximum biological yield per bed was obtained with sugarcane bagasse control bed 64.78 g/bed.The lowest yield was observed in woodchips (1:1) 4.6 g/bed. Based on mass obtained of G.lucidum the best substrates were ordered of like woodchips smaller than coir smaller thanÂ sugarcane. Â Conclusion Â Â The scope of this work is sea food wastes could be used to cultivate a medicinal mushroom while at the same time promoting environmental sustainability. Keywords: Mushroom, fishery waste, solid substrates, biological yield.